Biological and Cultural Tests for Control of Plant Diseases (B & C Tests). - IPS, Editor (Indian Phytopathology, 2002)
It is another excellent journal published annually by the American PhytopathologicalSociety since 1986. It has been started with the objectives to promote rapiddissemination of information on the effectiveness of cultivars, cultural practices, andbiocontrol agents used to control plant diseases as well as to improve biological and cultural testing and reporting; the primary object being publishing annual reports quickly so that the. results are available well in advance before planning the current season activities and also to provide a permanent reference for information on performance of biological and cultural controls of plant diseases. The added attraction of the journal is to print all accepted reports must having data of replicated plots or observations directly from the authors typed manuscript and will not be retyped or retouched mainly to reduce publication time and unnecessary expenditure.